Metastability in high entropy alloys - Kube, Sebastian A.; Schroers, Jan (Scripta materialia, 2020)
The high entropy effect is often insufficient to fully stabilize single-phase solid solutions (SPSS), yielding only few, mostly metastable SPSS. While the prospective space of favorable SPSS formation is smaller than commonly assumed, larger degrees of metastability can open up the vast High Entropy Alloy space. We argue that HEAs form metastable SPSS through polymorphic solidification upon rapid cooling. To quantify a HEA's metastability, we propose the critical cooling rate of SPSS formation RCSPSS, analogous to RCGlass. Thereby, we can compare multicomponent alloys by their metastability and SPSS or glass forming ability, which is determined by their underlying atomic dispersity.